2011
DOI: 10.1038/ajh.2010.266
|View full text |Cite
|
Sign up to set email alerts
|

Association of Arterial Stiffness Indexes, Determined From Digital Volume Pulse Measurement and Cardiovascular Risk Factors in Chronic Kidney Disease

Abstract: Our data demonstrate a significant association between CI-DVP, a new surrogate marker of arterial stiffness different from PWV, and renal function and cardiovascular risk factors in CKD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…22) CI, derived from our photoplethysmography system, may be clinically useful for evaluating arterial stiffness of small to medium sized arteries. 14,15) We showed that both large and small arterial stiffening occurs in pre-DM patients in the current study. In Table III of our study, we found that the HOMA index, rather than fasting glucose and HbA 1C , was an independent determinant for CI after adjusting for important confounders.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…22) CI, derived from our photoplethysmography system, may be clinically useful for evaluating arterial stiffness of small to medium sized arteries. 14,15) We showed that both large and small arterial stiffening occurs in pre-DM patients in the current study. In Table III of our study, we found that the HOMA index, rather than fasting glucose and HbA 1C , was an independent determinant for CI after adjusting for important confounders.…”
Section: Discussionmentioning
confidence: 80%
“…14,15) The stiffness index (SI), calculated from the digital volume pulse (DVP) measured by photoplethysmography, is an index of wave refl ections and also an acceptable marker for large arterial stiffness. 16,17) According to the 2010 American Diabetes Association (ADA) guideline for diagnosis and classifi cation of DM, 18) pre-DM patients have a HbA 1C level between 5.7% to 6.4%.…”
mentioning
confidence: 99%
“…Schillaci et al reported that there was an inverse relationship exists between GFR and stiffness of both central and peripheral arteries in hypertensive patients with normal renal function 23 . Our previous work showed that decrease of CI-DVP was associated with the increase in number of cardiovascular risk factors and CI-DVP was independently associated with eGFR 11 . Tian et al suggested that peripheral artery disease, defined as ABI <0.9, was a marker to predict the loss of residual renal function in patients receiving peritoneal dialysis 7 .…”
Section: Discussionmentioning
confidence: 94%
“…Compliance index derived from digital volume pulse (CI-DVP), measuring the relationship between volume and pressure changes in fingertip, is a surrogate marker of local and peripheral arterial stiffness. Previous studies have shown that there were significant associations among arterial compliance, cardiovascular risk factors and renal function in CKD patients, among CI-DVP, insulin resistance and inflammatory marker in pre-diabetes patients, and between CI-DVP and waist circumference in patients with nonalcoholic fatty liver disease 8 - 11 .…”
Section: Introductionmentioning
confidence: 95%
“…CKD is associated with progressive changes in central arterial extracellular matrix composition and collagen fiber configuration 33 and increased arterial stiffness. [34][35][36] Changes in the matrix structures of venous walls, however, have not been studied in CKD patients until our recent report describing qualitative patterns of collagen configuration. 7 This study has expanded on our previous qualitative description of collagen fiber patterns, 7 by quantifying two components of upper-extremity vascular fiber configuration, namely, anisotropy index and orientation angle.…”
Section: Discussionmentioning
confidence: 99%